Comparative informativity of computing methods of insulin resistance assessment - Kseneva, S. I.; Borodulina, E. V.; Trifonova, O. Yu; Fisenko, V. P.; Udut, Vladimir V. (Bulletin of experimental biology and medicine)
We conducted a comparative study of the calculated indices of insulin resistance HOMA-R, Caro, FGIR, and QUICKI in 29 healthy volunteers (mean age 26.21 +/- 0.93 years) with normal body mass index (23.34 +/- 0.55 kg/m2). Among the used methods for insulin resistance assessment, QUICKI is the only method that has characteristics required for the diagnostic criterium: low variability coefficient, 100% reproducibility, and minimum coefficient of variation.